Pengembangan LKM Berbasis Guided Discovery Learning (GDL) Pada Mata Kuliah Geometri Analitik - Ika Victoria Nalurita; Muhammad Jamaluddin (Universitas PGRI Adi Buana Surabaya, 2021)
This research was aimed to develop a valid, practical and effective student worksheet (LKM) based guided discovery learning (GDL) on Analytical Geometry course. This research was developmental research with a quantitative approach. Subjects of this research were Qomaruddin Gresik University S1 Mathematics Education students who take Analytical Geometry courses. Development of this LKM-based GDL was using the stages of Plomp. Stage generally consists of: (1) initial investigation, (2) design, (3) realization / construction, (4) testing, evaluation and revision and (5) implementation. Results showed that LKM-based GDL developed in this research has fulfilled the criteria of validity, practicality and effectiveness.